The National SOM Survey 1998 - SOM Institute, University of Gothenburg (University of Gothenburg, 2011)
Since 1986 the SOM-institute has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the thirteenth survey in this series. The SOM-institute is a collaboration between three departments at Göteborg University: the Institute for Journalism and Mass Communication, the Department of Political Science, and the School of Public Administration. The 1998 survey differs from the earlier ones since it includes two nation representative samples and uses two different mail questionnaires. One of the questionnaires mainly deals with questions on politics, economy and working life, while the other mainly deals with media, culture and health. One third of the questions asked in the two questionnaires are common for both samples, for example questions about media habits, political attitudes, leisure activities, and social background.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den trettonde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

Riks-SOM 1998 var den första SOM-undersökning som genomfördes som två undersökningar med två representativa urval och två olika formulär, där datainsamlingarna genomfördes parallellt och under identiska förhållanden. De båda formulären skiljer sig något åt i det att tyngdpunkten i Riks-1 ligger på politik och samhälle, medan Riks-2 har en tonvikt på frågor om medier, kultur och livsstil. En tredjedel av frågor är gemensamma för båda frågeformulären och kan därmed bearbetas med dubbel urvalsstorlek.

I Riks-SOM 1998 omfattar båda formulären sju olika frågeområden. Båda formulären omfattar frågeområdena: massmedier; politik och samhälle; fritid; samt bakgrundsfrågor. Politikformuläret (Riks-1) innehåller även: Sveriges förhållande till omvärlden; energi, kärnkraft, bilism och miljö; samt medievanor. Medieformuläret (Riks-2) tar också upp: hälsa och hälsorisker; radio, tv och andra medier; samt bibliotek.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1998
Riks-SOM 1998
Keywords: elections; val; housing; boende; mass media; massmedia; population migration; migration; occupations; yrken; participation; deltagande; public sector; offentlig sektor; international relations; internationella relationer; energy; energi; environment; miljö; health; hälsa; leisure time; fritid; finance; finans; religious attendance; religiöst deltagande; trust; förtroende; unemployment; arbetslöshet; voting; röstning; parliamentary elections; riksdagsval; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; membership; medlemskap; party identification; partiidentifikation; trade union membership; medlemskap i fackförening; public services; offentlig service; radio news; radionyheter; television channels; tv-kanaler; news; nyheter; television news; tv-nyheter; radioactive wastes; radioaktivt avfall; equipment; utrustning; privatization; privatisering; risk; risk; political participation; politiskt deltagande; international politics; internationell politik; television viewing; tv-tittande; language skills; språkfärdigheter; democracy; demokrati; defence and state security policy; försvars- och säkerhetspolitik; internal politics; inrikespolitik; labour market; arbetsmarknad; political parties; politiska partier; international cooperation; internationellt samarbete; air pollution; luftföroreningar; internet use; internetanvändning; european economic and monetary union; europeiska ekonomiska och monetära unionen; nuclear accidents; kärnkraftsolyckor; political leaders; politiska ledare